Generational Cohort and Work-Life Balance Policies Preference Among University Senior Teaching Staff in Ghana: Does Gender Matter? - Nicodemus Osei Owusu; Irene Combey; Nana Yaw Oppong (European Scientific Journal, ESJ, 2022)
The study sought to examine work-life balance (WLB) policies preference among generational cohorts concerning gender. Being quantitative, a population of 714 with a sample size of 333 was selected, but 306 responded. The main independent variable was gender while the dependent variable was work-life balance policies with four dimensions: Flexible Work Arrangement; Wellness and Personal Development; Leave Arrangement and Dependent Care Assistance. The data was analysed using inferential statistics. The study results showed that except for Wellness and Personal Development, where gender difference between males and females of Generation Y existed, gender did not differ significantly from the rest of the policies. Therefore, it was recommended that there should be equal treatment of both males and females in implementing WLB policies.